Students’ perspectives on using YouTube as a source of mathematical help: the case of ‘julioprofe’ - Esparza Puga, Danelly Susana (2021)
YouTube is one of the most popular sources of mathematical help among young students. In this study we explore the perspectives of engineering students on the use of YouTube videos with the intention of broadening our understanding of the general characteristics of the mathematical help that students obtain through this type of videos, particularly about the qualities of the sources of mathematical help that they prefer and trust. To conduct this exploration, we take as a reference the case of “julioprofe”, a YouTube channel on mathematics lessons with almost four million subscribers, which is widely known and used among Latin American students. Through focus groups, 22 engineering students from a Mexican university were interviewed about their experiences using the julioprofe videos as a source of mathematical help. The results suggest that the mathematical help that students get from these YouTube videos is a type of multifunctional help, always available, private, easy to use and self-paced. It is a type of mathematical help that students cannot obtain from more traditional school contexts. We argue that these features contribute to making YouTube such a popular source of mathematics help among contemporary students.